Perbedaan Kemandirian Perilaku Anak Sulung dan Anak Bungsu Siswa SMP Negeri 1 Sungai Beremas - Fudhla, Miftahul; Zikra, Zikra (Lembaga Yasin AlSys, 2023)
Behavioral independence is a child's attitude or actions in determining and making decisions based on their own desires without depending on other people. However, what happens in the field is that students still do not have the confidence to make decisions regarding their education. One factor that causes this is birth order. This means that in the family parents give children the opportunity, trust and freedom to act based on the child's position or birth order. The aim of this research is to describe the behavior of the eldest and youngest children of SMP Negeri 1 Sungai Beremas students and see whether or not there are differences in the behavior of the eldest and youngest children. The research method used is a quantitative method with a descriptive-comparative analysis approach. The population in this study was 170 students and the sample was 119 students who were the oldest and youngest students. Samples were taken using the Slovin formula. The sampling technique used is probability sampling with simple random sampling. The instrument used is a behavioral independence questionnaire with an interval scale. The research results obtained were that the oldest and youngest children had an average of behavioral independence in the high category with an average result of 51 and 53. Meanwhile, the results of the t test analysis showed that there was a difference in behavioral independence between the eldest and youngest children with a significance of 0.015 with the mean behavioral independence of the eldest child of 101.56 and the mean behavioral independence of the youngest child of 105.17. So it can be concluded that the youngest child is more independent than the eldest child.